East
CentricArch
Sign in
Ask The Question
English
French
Spanish
Portuguese
Polish
Romanian
Mathematics
niah
Apr 20, 2018, 7:02:50 PM
30
Given that f(x) = -x+4 and g(x)=-2x-3, solve for f(g(x)) when x=2
+3
(
1
) Answers
x3undiscovered
Apr 21, 2018, 5:23:14 AM
g(2) = -4-3 = -7 So f(g(2)) = f(-7) = 7+4 = 11
Add answer
Sign in
Sign up
Related Questions
Given that f(x) = -x+4 and g(x)=-2x-3, solve for f(g(x)) when x=2
Given that f(x) = 2x + 1 and g(x) = −5x + 2, solve for f(g(x)) when x = 3.
Given that f(x) = 2x 1 and g(x) = −5x 2, solve for f(g(x)) when x = 3.
Given that f(x) = 2x + 5 and g(x) = x − 7, solve for f(g(x)) when x = −3.
Given that f(x) = x2 − 4x − 3 and g(x) = x+3/4 , solve for f(g(x)) when x = 9.
Given that f(x) = x2 + 2x + 3 and g(x) = quantity of x plus four, over three, solve for f(g(x)) w...
F(x)=-x+4 and g(x)=-2x-3 solve for f(g(x)) x=2
Given that f(x)= x^2-3x+3 and g(x)=x-1/4 solve for f(g(x)) when x=5 a. -3 b. 1 c. 7 d. 13
given that f(x) =5x-10 and g(x)=x+3 solve for f(g(x) when x=-1 a.-30 b.0 c.10 d.12
Given that f(x) = 2x + 1 and g(x) = the quantity of 3x minus 1, divided by 2, solve for g(f(3))